Interaction of fungicides with the entomopathogenic fungus Isaria - D'alessandro, Celeste Paola (2011)
The effects of eight commonly used fungicides: propamocarb, fenarimol, triadimefon, procimidone, azoxystrobin, carbendazim, cooper oxychloride and Trichoderma harzianum on germination, mycelial growth and virulence of Isaria fumosorosea (Wize) Brown & Smith (Ascomycota: Hypocreales) was studied. The greatest effect on germination was observed by azoxystrobin, followed by carbendazim, triadimefon and procimidone. Propamocarb, fenarimol, cooper oxychloride and T. harzianum did not affect conidial germination with germinations of 95, 93, 79 and 84%, respectively. Virulence was evaluated against early fourth instar nymphs of Trialeurodes vaporariorum (Hemiptera: Aleyrodidae). The mix containing fungal conidial suspensions plus cooper oxychloride or fenarimol presented a significant reduction in the mortality in comparison with spore suspension itself. This study suggests that the most appropriate fungicides for use in Integrated Pest Management Programs against T. vaporariorum in combination with I. fumosorosea are propamocarb and T. harzianum.